2005
DOI: 10.1002/eqe.485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil interaction on the performance of liquid column dampers for seismic applications

Abstract: SUMMARYThe e ects of soil-structure interaction (SSI) while designing the liquid column damper (LCD) for seismic vibration control of structures have been presented in this study. The formulation for the inputoutput relation of a exible-base structure with attached LCD has been presented. The superstructure has been modelled by a single-degree-of-freedom (SDOF) system. The non-linearity in the oriÿce damping of the LCD has been replaced by equivalent linear viscous damping by using equivalent linearization tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The soil has the effect of lowering the system's modal frequencies, a fact reported in numerous studies on SSI. [1][2][3][4]9,12 The tower's first and third modes of displacement response show a reduction in frequency with reduction in soil stiffness (shear modulus). There is an even greater reduction in the second modal frequency of the tower displacement response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil has the effect of lowering the system's modal frequencies, a fact reported in numerous studies on SSI. [1][2][3][4]9,12 The tower's first and third modes of displacement response show a reduction in frequency with reduction in soil stiffness (shear modulus). There is an even greater reduction in the second modal frequency of the tower displacement response.…”
Section: Discussionmentioning
confidence: 99%
“…5 The use of SSI in design is usually restricted to buildings in seismic zones. [6][7][8][9] However, wind turbines contain moving parts and must sustain continuous vibration-induced forces throughout their operational life. Novak and Hifnawy 10,11 showed that the response of a structure when subject to a dynamic wind loading can be affected by SSI.…”
Section: Introductionmentioning
confidence: 99%
“…x g , x 0 , φ y , and x denote, respectively, the free-field displacement of the soil, horizontal displacement, and rotation of the soil-foundation interface, and the structural relative displacement with respect to foundation in the time domain. From this decomposition, the dynamic equilibrium equations for the movement of the liquid inside the pressurized damper, the translation of the structural mass and the displacements/rotations at the base are established as proposed by Ghosh and Basu (2005). The equation of motion of the liquid column is given by…”
Section: Soil Structure Interaction With Ptlcdmentioning
confidence: 99%
“…When these interaction effects are included, it is necessary to evaluate the SSI interference in the performance of the TLCD for seismic applications. Luco (1998) and Ghosh and Basu (2005) using impedance functions that consider the three systems (soil-structure-damper), analyzed these effects. After studies such as these, in which the influence of SSI on vibration control is evidenced, Mousavi et al (2013), Farshidianfar and Soheili (2013), and Ozuygur and Gunduz (2018) applied optimization methods to define optimal parameters for the passive device connected to a structure subject to seismic action and under the influence of site conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the main dynamic load considered in these structures is due to the wind. Just like the random action of the wind, efforts have been applied to the dynamic analysis of structures with TLCD for the control of earthquake vibrations (Gosh and Basu, 2005;Chakraborty et al, 2012;Mendes et al, 2019;Espinoza et al, 2018). For a better performance of the damper, (Gosh and Basu, 2004;Sonmez et al, 2016) propose a different composition, in which the TLCD is connected to the primary structure using an adaptive spring.…”
Section: Introductionmentioning
confidence: 99%